ERB WEBSITE DESIGN APPLICATIONS USING JOOMLA 1.5 AND APPSERV - Ridzky Azhari; Sutarno, SKom, MMSI Sutarno, SKom, MMSI (Jurnal Sistem Informasi, 2010)
In making ERB website, the author uses Joomla software. Jomla is a CMS (ContentManagement System) which provides convenience to its users to manage and makechanges to the content of a given dynamic website without the prior knowledge aboutmatters of a technical nature.By using Joomla, the website can easily be made without having to make source codeor other syntax syntax commonly used in making website in general. Difficulty inmaking this website was to find a suitable module to display images from the gallerymenu, look for a suitable template for this website, and edit the background images.